INSTITUTIONALMEDIATION OF THE CONFLICTS IN THE CAUCASUS - SHELEST, Hanna (CENTRAL ASIA AND THE CAUCASUS, 2012)
The peaceful settlement of international conflicts has gained strong support and recognition as one of the fundamental principles of international relations. Different means and methods of mediation have been used by practitioners over the years. As a form of conflict management and peaceful settlement, mediation is very much in line with contemporary international relations. In the present-day interconnected multistate system, which includes a lot of broken agreements and unstructured conflicts, prevention or taking only one side may lead to a future struggle, or states may act only in their own interests and not always agree to enter negotiations. In such situations, mediation may be the only viable option for the sides are willing to accept. Conflicting parties usually face two questions: should they accept mediation and, if yes, whose mediation should they accept? Parties agree to mediation, expecting that it will work in their interests. One of the most widespread motives, in our opinion, is the expectation that the mediator can reach a better result than the one that might ensue if the conflict continues. In this article, we propose a classification of mediation based on the principle of subjectivity. World history and mediation practice have proven that, in most situations, the main factor influencing the decision to accept or not accept mediation is the individuality of the mediator and its subjectivity. We provide a classification based on whether the mediator is an individual, state, or international organization. In this particular article, we will talk only about institutional mediation through the prism of peaceful settlement of the conflicts in Caucasian states—Georgia and Azerbaijan. Institutional mediation is mediation initiated by an international organization or institution. Nowadays this type of mediation is the most developed for a number of objective and subjective reasons. The subjective reasons include perception of the international organization as an impartial, even neutral side that represents the opinion of many countries and does not follow its own interests, except for the attempt to restore peace and security in the region. The objective reasons are the availability of more instruments of persuasion, mechanisms of mediation, and re-sources for fulfilling the mediation mission, as well as international legal and institutional consolidation of the mission. Moreover, as practice has shown, the specific features of the international organization’s work do not have a decisive influence on the effectiveness of the mediation efforts.